A Systematic Review and Meta-Analysis of Conditioned Pain Modulation in Children and Young People with Chronic Pain - Christina Liossi; Helen Laycock; Kanmani Radhakrishnan; Zara Hussain; Daniel Eric Schoth (MDPI AG, 2024)
Background/Objectives: Conditioned pain modulation (CPM) is a psychophysical experimental measure of the endogenous pain inhibitory pathway in humans, wherein one pain stimulus (the conditioning stimulus) is used to inhibit an individual's perception of a second painful (test) stimulus. Research provides evidence of impaired endogenous inhibitory pain responses in adults with chronic pain. CPM is now increasingly applied in paediatric research and clinical practice. The primary aim of this systematic review was to examine the efficacy of CPM in paediatric chronic pain populations (6-24-year-olds) compared to pain-free children and young people (CYP). Methods: The protocol was registered on PROSPERO (CRD42020221927). A systematic search of seven databases was conducted from database inception to 20th June 2024. Study inclusion criteria were as follows: (i) recruited a sample of CYP aged 6 to 24 (inclusive) with chronic pain or who were pain-free; and (ii) applied a CPM paradigm comprising both a painful test and conditioning stimuli that were sufficiently detailed to allow for replication,(iii) adhered to a study design of randomised control trial, case control or cohort study, including cross-sectional or longitudinal; (iv) available in the English language. Study exclusion criteria were: (i) The CPM paradigm used a non-painful test or conditioning stimulus only; and (ii) was only available as an abstract, letter, poster, editorial, case report, or review with or without meta-analyses. Risk of bias was assessed using the Appraisal Tool for Cross Sectional Studies (AXIS). Meta-analyses were conducted in Comprehensive Meta Analysis 3.0 using random effects models to compare the overall CPM responses in CYP with chronic pain conditions to healthy control CYP. Results: Thirty-two studies were eligible for inclusion, six of which were included in one or more meta-analysis (n = 407 chronic pain, n = 205 control). Meta-analysis revealed significantly weaker CPM responses in CYP with a variety of chronic pain conditions compared to healthy controls (standardized mean difference (SMD) = 0.352), and significantly weaker CPM responses in CYP with abdominal pain conditions compared to healthy controls (SMD = 0.685). No significant difference in CPM response was found between CYP with migraine and healthy controls (SMD = −0.201). Conclusions: Variable results were found across individual studies, and the meta-analysis of the small number of eligible studies provides tentative evidence for impaired CPM in CYP with chronic pain compared to healthy controls. Further research is clearly needed. In particular, studies should present CPM results separately for different age groups, ethnic groups, and sexes, as these variables shape clinical pain responses.